Etude de l'effet toxique du cadmium chez le polychète Nereis diversicolor (O.F. Müller,1776) : paramètres biochimiques et caractérisation des sédiments - Kouache Fateh; Ounassi Nor El Islem (My University, 2023)
Environmental pollution by heavy metals present a major risk to living beings living. Cadmium is a toxic heavy metal, and is relatively abundant in the Annaba region. The objective of this study is to evaluate the sensitivity and/or resistance of Nereis diversicolor to stress induced by cadmium and its impact on the biochemical composition (carbohydrates, Proteins). Three aspects were examined: -Cadmium toxicity bioassays at different concentrations (30- 45- 75 and 120) mg/L added to N. diversicolor culture water in order to estimate lethal concentrations LC10 :31.04 (25.86-37.24), CL25 :63.24 (52.7-75.88), CL50 :139.63(116.35 - 167.55) and CL90: 629.50 (524.58-755.4) after 48h of exposure. The results obtained show the mortality of the species studied with a dose-response relationship. This suggests that N. diversicolor is a cadmium-resistant species. -Then, we determined the impact of this xenobiotic on carbohydrate and proteins levels. The results show a significant reduction in these levels after treatment for 48 hours. -It is well known that depth, seasonality, sediment particle size and content in organic matter are the most important factors controlling the distribution of benthic macrofauna on sandy coasts. For this, a particle size analysis and a measurement of organic matter were carried out during this study. Four stations on the eastern Algerian coast were chosen (Sidi Salem, El Chatt, El Battah and El Mordjene). Particle size analyzes revealed the presence of three granular elements in these samples which vary significantly: sand, silt and clay. Indeed, there is a remarkable fluctuation of organic matter which varies significantly between 1.66% to 8.33%. ----------------------------------------------------------------------------------------------------------------------------------------------------------------- يشكل التلوث البيئي بالمعادن الثقيلة خطراً كبيراً على الكائنات الحية. الكادميوم معدن ثقيل سام، ومتوفر نسبياً في منطقة عنابة. الهدف من هذه الدراسة هو تقييم حساسية و / أو مقاومة Nereisdiversicolor للإجهاد الناجم عن الكادميوم وتأثيره على التركيب الكيميائي الحيوي (الكربوهيدرات،البروتينات). تم فحص ثلاثة جوانب: -المقايسات الحيوية لسمية الكادميوم بتركيزات مختلفة (30-45-75 و 120) ملجم / لتر مضاف إلى مياه التربية N.diversicolor لتقدير التركيزات المميتة CL10: 31.04 (25.86- 37.24), CL25: 63.24 (52.7-75.88) ، CL50:139.63(116.35-167.55)وCL90: 629.50 (524.58 -755.4) بعد 48 ساعة من التعرض. تظهر النتائج التي تم الحصول عليها معدل النفوق في الأنواع المدروسة بعلاقة بين الجرعة والاستجابة. يشير هذا إلى أنN.diversicolor هو نوع مقاوم للكادميوم. -ثم حددنا تأثير هذه الملوثات على مستويات الكربوهيدرات و البروتينات. تظهر النتائج انخفاضًا ملحوظًا في هذه المستويات بعد العلاج لمدة 48 ساعة. -من المعروف أن العمق ، الموسمية ، حجم جزيئات الرواسب ومحتواها في المواد العضوية أهم العوامل التي تتحكم في توزيع الكائنات الحية القاعية على السواحل الرملية. لهذا ، تم إجراء تحليل حجم الجسيمات وقياس المادة العضوية خلال هذه الدراسة. تم اختيار أربع محطات على الساحل الشرقي للجزائر (سيدي سالم ، الشط ، البطاح والمرجان). كشفت تحليلات حجم الجسيمات عن وجود ثلاثة عناصر حبيبية في هذه العينات والتي تختلف اختلافًا كبيرًا: الرمل ، الطمي والطين. في الواقع ، نشهد تقلبًا ملحوظًا في المادة العضوية متنوعًا بشكل ملحوظ بين 1.66٪ إلى 8.33٪. ------------------------------------------------------------------------------------------------------------------------------------------------------------ يشكل التلوث البيئي بالمعادن الثقيلة خطراً كبيراً على الكائنات الحية. الكادميوم معدن ثقيل سام، ومتوفر نسبياً في منطقة عنابة. الهدف من هذه الدراسة هو تقييم حساسية و / أو مقاومة Nereisdiversicolor للإجهاد الناجم عن الكادميوم وتأثيره على التركيب الكيميائي الحيوي (الكربوهيدرات،البروتينات). تم فحص ثلاثة جوانب: -المقايسات الحيوية لسمية الكادميوم بتركيزات مختلفة (30-45-75 و 120) ملجم / لتر مضاف إلى مياه التربية N.diversicolor لتقدير التركيزات المميتة CL10: 31.04 (25.86- 37.24), CL25: 63.24 (52.7-75.88) ، CL50:139.63(116.35-167.55)وCL90: 629.50 (524.58 -755.4) بعد 48 ساعة من التعرض. تظهر النتائج التي تم الحصول عليها معدل النفوق في الأنواع المدروسة بعلاقة بين الجرعة والاستجابة. يشير هذا إلى أنN.diversicolor هو نوع مقاوم للكادميوم. -ثم حددنا تأثير هذه الملوثات على مستويات الكربوهيدرات و البروتينات. تظهر النتائج انخفاضًا ملحوظًا في هذه المستويات بعد العلاج لمدة 48 ساعة. -من المعروف أن العمق ، الموسمية ، حجم جزيئات الرواسب ومحتواها في المواد العضوية أهم العوامل التي تتحكم في توزيع الكائنات الحية القاعية على السواحل الرملية. لهذا ، تم إجراء تحليل حجم الجسيمات وقياس المادة العضوية خلال هذه الدراسة. تم اختيار أربع محطات على الساحل الشرقي للجزائر (سيدي سالم ، الشط ، البطاح والمرجان). كشفت تحليلات حجم الجسيمات عن وجود ثلاثة عناصر حبيبية في هذه العينات والتي تختلف اختلافًا كبيرًا: الرمل ، الطمي والطين. في الواقع ، نشهد تقلبًا ملحوظًا في المادة العضوية متنوعًا بشكل ملحوظ بين 1.66٪ إلى 8.33٪. ---------------------------------------------------------------------------------------------------------------------------------------------------------------- La pollution de l'environnement par les métaux lourds présente un risque majeur pour les êtres vivants. Le cadmium est un métal lourd toxique, et est relativement abondant dans la région d’Annaba. L’objectif de cette étude est d’évaluer la sensibilité et/ou la résistance de Nereisdiversicolor au stress induit par le cadmium et son impact sur la composition biochimique (glucides, protéine). Trois aspects ont été examinés : -Les bioessais de toxicité du cadmium à différentes concentrations (30- 45- 75 et 120) mg/L ajoutées à l'eau d'élevage de N. diversicolor afin d’estimer les concentrations létales CL10 :31.04 (25,86- 37,24), CL25 :63,24 (52,7-75,88), CL50 :139,63(116,35-167,55) et CL90 : 629,50(524,58-755,4) après 48h d’exposition. Les résultats obtenus montrent la mortalité de l’espèce étudiée avec une relation dose-réponse. Ce qui suggère que N. diversicolor est une espèce résistante au cadmium. -Ensuite, nous avons déterminé l’impact de ce xénobiotique sur les teneurs de glucides et de protéines. Les résultats montrent une diminution significative de ces teneurs après traitement de 48h. -Il est bien connu que la profondeur, la saisonnalité, la taille des particules sédimentaires et la teneur en matière organique sont les facteurs les plus importants contrôlant la distribution du macrofaune benthique des côtes sableuses. Pour cela, une analyse granulométrique et une mesure de la matière organique ont été effectués durant cette étude. Quatre stations du littoral Est Algérien ont été choisis (Sidi Salem, El Chatt, El Battah et El Mordjene). Les analyses granulométriques ont révélé la présence de trois éléments granulaires dans ces échantillons qui se varient significativement : le sable, la limon et argile. En effet, on assiste à une fluctuation remarquable de la matière organique qui varie significativement entre 1.66 % à 8,33%.